Interference aware frequency assignment and association control for uplink and downlink traffic in WLAN. (29th May 2019) - Tewari, Babul P.; Ghosh, Sasthi C.
In IEEE 802.11 wireless local area network, interference management and association control play a significant role to determine the network performance. The problem of interference management becomes more challenging in simultaneous presence of uplink and downlink communication traffic. This paper addresses the issue of interference not only from the perspective of access points but also from the perspective of clients considering a mixed traffic. We first define several types of transmission conflicts influenced by different communication traffic and based on that we model effective interference. Importance of such effective interference has been described through a motivational example. We then propose an efficient greedy algorithm that jointly considers association control and frequency assignment to avoid the effective interference for maximising the aggregate throughput. The novelty of the proposed approach is evaluated through extensive simulations. We also have shown that the proposed algorithm gives comparable results with other existing approaches.